Force as a facilitator of integrin conformational changes during leukocyte arrest on blood vessels and antigen-presenting cells. - Alon, R; Dustin, M (2007)
Integrins comprise a large family of cell-cell and cell-matrix adhesion receptors that rapidly modulate their adhesiveness. The arrest of leukocyte integrins on target vascular beds involves instantaneous conformational switches generating shear-resistant adhesions. Structural data suggest that these integrins are maintained in low-affinity conformations and must rapidly undergo conformational switches transduced via cytoplasmic changes ("inside-out" signaling) and simultaneous ligand-induced rearrangements ("outside-in"). This bidirectional activation is accelerated by signals from endothelial chemoattractants (chemokines). Recent studies predict that shear forces in the piconewton (pN) range per integrin can facilitate these biochemical switches. After extravasation, antigen recognition involves smaller internal forces from cytoskeletal motors and actin polymers forming the immune synapse. In this review, we address how forces facilitate allosteric integrin activation by biochemical signals. Evidence suggests that preformed cytoskeletal anchorage rather than free integrin mobility is key for force-enhanced integrin activation by chemokines and TCR signals.